Confronting Genocide: Judaism, Christianity, Islam - Jacobs, Steven Leonard (Lexington Books, 2009)
Confronting Genocide: Judaism, Christianity, Islam is the first collection of essays by recognized scholars primarily in the field of religious studies to address this timely topic. In addition to theoretical thinking about both religion and genocide and the relationship between the two, these authors look at the tragedies of the Holocaust, the Armenian Genocide, Rwanda, Bosnia, and the Sudan from their own unique vantage point. In so doing, they supply a much needed additional contribution to the ongoing conversations proffered by historians, political scientists, sociologists, psychologists, and legal scholars regarding prevention, intervention, and punishment.